MODELING OF THE DYNAMIC OPERATION MODE OF AN AUTONOMOUS WIND POWER INSTALLATION WITH AN ASYNCHRONOUS GENERATOR - DON, NATALIA; POGREBNIAK, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents the results of modeling the dynamic operation mode of an autonomous wind power installation with an asynchronous generator. Currently, the starting modes of autonomous wind power plants of both small and medium capacity have been sufficiently studied; however, the main operating modes of autonomous wind power plants still require further investigation. Consequently, modeling the dynamic operating modes of autonomous wind power plants with an asynchronous generator is relevant. A visually-oriented block diagram of the autonomous wind power installation with an asynchronous generator was created in the MATLAB/Simulink environment, and the operation modes were simulated, determining the main characteristics. The results of the study indicate the adequacy of the applied model, which allows for the study of dynamic operating modes that enable optimal tuning of the control system to enhance energy efficiency both of the wind power installation and the autonomous system as a whole. Further research may be directed towards examining the operating modes of wind power installations as part of a wind power station. The model of an autonomous wind power installation with an asynchronous generator, implemented in the Matlab/Simulink environment, will allow for the investigation of the energy characteristics of the installation based on available technical parameters and can be used in the educational process in training specialists in the field of «Electrical Engineering», particularly in the laboratory practice of the courses «Electrical Machines and Apparatus» and «Fundamentals of Wind Energy».